A PDA-modified BiVO4 photoelectrocatalyst and its preparation method
Patent Information
- Application Number
- CN202611187268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]针对现有 光电催化材料存在光生载流子复合率较高、界面电荷传输效率不足、表面反应动力学较慢以及长期光电催化稳定性较差的问题,本发明提供一种 PDA 修饰
的光电催化材料及其制备方法
[0031]本发明通过在 表面形成 PDA 修饰层,使 PDA 作为
与 NiFeOx助催化剂之间的功能性桥接层,能够改善二者之间的界面结合状态,有利于提高助催化剂负载稳定性。采用光诱导方式在
表面形成 PDA 修饰层,PDA 修饰后
的主体晶相和纳米结构未被破坏,同时可以改善材料表面状态,提高可见光捕捉能力和光电转化效率。
Smart Images

Figure CN122999212A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photoelectrocatalytic materials technology, specifically a PDA-modified... Photocatalytic materials and their preparation methods. Background Technology
[0002] With the increasing prominence of energy shortages and environmental pollution, the development of photoelectrocatalytic materials that can efficiently utilize solar energy has become an important research direction in the fields of new energy and environmental governance. Photoelectrocatalysis technology utilizes semiconductor materials to absorb light energy and generate photoelectrons and holes, thereby driving water splitting, organic pollutant degradation, and other redox reactions. It has advantages such as being clean, sustainable, and having a wide range of applications.
[0003] Bismuth vanadate ( This is a typical visible-light-responsive semiconductor photoelectrocatalyst material with a band gap of approximately 2.4 eV, capable of absorbing some visible light; simultaneously, It also has the characteristics of relatively readily available raw materials, low toxicity, good chemical stability and positive valence band potential, so it has received widespread attention in the fields of photoelectrocatalytic water splitting, photoelectrocatalytic oxidation and environmental pollutant treatment.
[0004] However, unmodified Photoelectrodes still have significant performance defects. On the one hand, Photogenerated electrons and holes readily recombine, leading to a reduction in the number of effective charge carriers actually participating in surface catalytic reactions; on the other hand... The charge migration ability is weak, the hole diffusion length is short, and the interfacial charge transport efficiency is low, which limits its photocurrent density and photoelectrocatalytic reaction efficiency. These problems make... The actual photoelectrocatalytic performance of the photoelectrode is still significantly lower than the theoretical level, which affects its further application.
[0005] Therefore, it is necessary to provide a new Photoelectrocatalytic materials and their preparation methods to improve existing... To address the problems of severe recombination of photogenerated carriers, low charge transport efficiency, and insufficient photocurrent density in photoelectrodes, a photoelectrode material with high photocatalytic performance and good stability is obtained. Summary of the Invention
[0006] In response to the existing Photoelectrocatalytic materials suffer from problems such as high recombination rates of photogenerated carriers, insufficient interfacial charge transport efficiency, slow surface reaction kinetics, and poor long-term photoelectrocatalytic stability. This invention provides a PDA-modified... Photoelectrocatalytic materials and their preparation methods are described. These photoelectrocatalytic materials utilize... A PDA-modified layer is introduced onto the surface, and NiFeOx cocatalyst is further loaded, so that the PDA-modified layer acts as a catalyst. A functional bridging layer between NiFeOx and NiFeOx improves the interfacial bonding state, promotes the separation and transport of photogenerated carriers, and enhances photoelectrocatalytic efficiency and long-term stability.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] This invention provides a PDA modification The photoelectrocatalytic material includes a conductive substrate and a substrate supported on the surface of the conductive substrate. Nanoparticle layer, formed in the A PDA modification layer on the surface of the nanoparticle layer and a NiFeOx cocatalyst layer supported on the PDA modification layer; the PDA modification layer is located on the nanoparticle layer. Between the nanoparticle layer and the NiFeOx cocatalyst layer, and respectively with the... The nanoparticle layer is in contact with the NiFeOx cocatalyst layer.
[0009] Preferably, the The layer has a porous structure composed of interconnected nanoparticles and / or short nanorods; the PDA-modified layer is formed by dopamine reacting under light conditions. Polymerization occurs on the surface of the layer, forming a layer that at least partially covers the surface. The surface of the layer; the PDA modification layer is used to connect the Layer and the NiFeO x The co-catalyst layer promotes the Photogenerated holes generated in the layer are directed towards the NiFeO x Catalyst layer transfer.
[0010] Preferably, the conductive substrate is FTO conductive glass.
[0011] Preferably, the The nanoparticle layer is formed by introducing a vanadium source into the BiOI precursor and then calcining it.
[0012] Preferably, the PDA modification layer is formed by photoinduced polymerization of dopamine hydrochloride in a weakly alkaline Tris-HCl buffer.
[0013] Preferably, the NiFeOx cocatalyst layer is formed by pulse photoelectrodeposition of an electrolyte containing iron and nickel salts.
[0014] The present invention also provides a PDA modification The preparation method of the photoelectrocatalytic material includes the following steps:
[0015] S1, with KI and Dissolve in deionized water, and add nitric acid to adjust the pH to obtain mixed solution A;
[0016] S2, dissolve p-benzoquinone in anhydrous ethanol to obtain solution B;
[0017] S3, add solution B dropwise to mixed solution A and stir to obtain BiOI electrodeposition solution;
[0018] S4, using a conductive substrate as the working electrode, electrodeposition is performed in the BiOI electrodeposition solution to obtain a conductive substrate with BiOI nanoparticles deposited on its surface.
[0019] S5, a vanadium source is introduced onto the surface of a conductive substrate with deposited BiOI nanoparticles, followed by calcination and impurity removal to obtain... Photoelectrode;
[0020] S6, the The photoelectrode was immersed in a Tris-HCl buffer solution containing dopamine hydrochloride and subjected to photo-induced treatment under simulated sunlight to obtain... Photoelectrode;
[0021] S7, the The photoelectrode was immersed in an electrolyte containing iron and nickel salts, and pulsed photoelectrodeposition was performed under cyclic illumination to obtain a NiFeOx-loaded PDA-modified PDA. Photocatalytic materials.
[0022] Preferably, in step S1, the KI, The mass-to-volume ratio of the deionized water is 1.68 g: 0.4–1.0 g: 25 mL; adjust the pH to 1.5–2.0.
[0023] Preferably, in step S2, the mass-to-volume ratio of p-benzoquinone to anhydrous ethanol is 0.2–4.0 g: 10 mL.
[0024] Preferably, in step S3, solution B is added dropwise to mixed solution A at a rate of 0.5 to 2 mL / min.
[0025] Preferably, in step S4, the conductive substrate is FTO conductive glass, and the electrodeposition is performed using a three-electrode system, wherein the FTO conductive glass is used as the working electrode, the Pt wire is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode; the applied bias voltage for electrodeposition is -0.05 V to -0.15 V, and the electrodeposition charge is 0.6 to 0.8 C.
[0026] Preferably, in step S5, the vanadium source is a dimethyl sulfoxide solution of vanadium acetylacetonate; the calcination temperature is 400–500 °C, and the calcination time is 90–180 min; after calcination, the vanadium is soaked in NaOH solution or KOH solution to remove impurities.
[0027] Preferably, in step S6, the Tris-HCl buffer solution containing dopamine hydrochloride is prepared by dissolving dopamine hydrochloride and Tris-HCl in deionized water and adjusting the pH to 8.0–9.0; the simulated sunlight is AM 1.5G, and the light intensity is [missing information]. The photo-induced treatment time is 1–4 h.
[0028] Preferably, in step S7, the iron salt is ferrous acetate and the nickel salt is nickel acetate; the concentration of the iron salt in the electrolyte is 0.1–1.0 mM and the concentration of the nickel salt is 0.01–0.2 mM; the pulsed photoelectrodeposition is performed under the condition of a reversible hydrogen potential of 0 V, the light cycle is 5–20 s on and 10–40 s off, and the deposition time is 10–40 min.
[0029] The present invention also provides the above-mentioned PDA modification. Applications of photoelectrocatalytic materials in photoelectrocatalytic water oxidation, photoelectrocatalytic oxygen evolution reaction, pollutant degradation, or photoelectrocatalytic organic synthesis reactions.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] This invention, through A PDA modification layer is formed on the surface, enabling the PDA to function as... A functional bridging layer between the catalyst and the NiFeOx cocatalyst can improve the interfacial bonding state between them, which is beneficial to improving the loading stability of the cocatalyst. Photoinduced methods are used in... A PDA modification layer is formed on the surface. After PDA modification... The main crystalline phase and nanostructure are not destroyed, and the surface state of the material can be improved, thereby enhancing the visible light capture capability and photoelectric conversion efficiency.
[0032] This invention, through Further loading of NiFeOx cocatalyst onto the surface can accelerate the surface water oxidation reaction kinetics, reduce interfacial charge recombination, and improve the utilization efficiency of photogenerated carriers. The PDA modification obtained in this invention... The photoelectrocatalytic material exhibits better photocurrent retention during long-term storage or continuous photoelectrocatalytic testing, indicating that the PDA modification layer can improve photocurrent retention to a certain extent. Long-term stability of basic photoelectrocatalytic materials. Attached Figure Description
[0033] Figure 1 Scanning electron microscope images of different photoelectrode materials.
[0034] Figure 2 for Photoelectrode and Characterization diagram of the phase structure and surface chemical composition of the photoelectrode.
[0035] Figure 3 for Photoelectrode and Figure showing the test results of the light absorption and photoelectric conversion performance of the photoelectrode.
[0036] Figure 4 for Photoelectrode and Bandgap fitting diagram of photoelectrode.
[0037] Figure 5 for Photocatalytic materials and The change in photocurrent density of the photoelectrocatalytic material after different resting times.
[0038] Figure 6 Prepared under different pH conditions of BiOI electrodeposition solutions Photocurrent stability test curves of photoelectrocatalytic materials.
[0039] Figure 7 Prepared using different BiOI electrodeposition charges Photocurrent stability test curves of photoelectrocatalytic materials.
[0040] Figure 8 Prepared using different BiOI electrodeposition charges Electrochemical impedance spectroscopy of photoelectrocatalytic materials. Detailed Implementation
[0041] The technical solution of the present invention will be further described below with reference to embodiments. It should be understood that the following embodiments are only for illustrating the present invention and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions, conventional adjustments or parameter optimizations made based on the concept of the present invention should fall within the scope of protection of the present invention.
[0042] Unless otherwise stated, all reagents used in the following examples are of analytical grade or higher purity, the water used is deionized water, the FTO is fluorine-doped tin oxide conductive glass, and the simulated sunlight is AM 1.5G illumination.
[0043] In this invention, PDA represents polydopamine. represents bismuth vanadate, and NiFeOx represents nickel-iron oxide cocatalyst. The photoelectrocatalytic material prepared by this invention can be represented as... Photoelectrode, also known as Photoelectrocatalytic materials, both referring to materials sequentially formed on an FTO conductive substrate. A composite photoelectrode consisting of a layer, a PDA modification layer, and a NiFeOx cocatalyst layer.
[0044] Example 1
[0045] This embodiment provides a The preparation method of photoelectrocatalytic materials includes the following steps:
[0046] (1) Preparation of BiOI electrodeposition solution
[0047] Weigh 1.668 g of KI and add it to 25 mL of deionized water, stirring until completely dissolved; then weigh 0.485 g of KI... Slowly add the above KI solution and continue stirring to obtain... Mixed solution.
[0048] To the Add 20 μL of 69% nitric acid to the mixed solution to adjust the pH to 1.65, thus obtaining mixed solution A.
[0049] Take another 0.248 g of p-benzoquinone, add it to 10 mL of anhydrous ethanol, stir to dissolve, and obtain solution B.
[0050] Solution B was slowly added dropwise to mixed solution A at a rate of 1 mL every 2 min, with continuous stirring during the addition process. After the addition was completed, stirring was continued for 20 min to obtain the BiOI electrodeposition solution.
[0051] (2) Preparation of BiOI / FTO precursor electrode
[0052] Electrodeposition was performed using a three-electrode system, in which FTO conductive glass was used as the working electrode, platinum wire as the counter electrode, and Ag / AgCl electrode as the reference electrode.
[0053] The FTO conductive glass was immersed in the BiOI electrodeposition solution obtained in step (1), and electrodeposition was performed under an applied bias voltage of -0.1 V. Electrodeposition was stopped when the electrodeposition charge reached 0.7 C. The FTO conductive glass was then removed, and its surface was rinsed sequentially with deionized water and anhydrous ethanol, and then dried at room temperature to obtain a BiOI / FTO precursor electrode with BiOI nanoparticles deposited on its surface. The applied bias voltage can also be -0.118 V, and the preferred electrodeposition charge is 0.7 C.
[0054] (3) Fabrication of photoelectrodes
[0055] Weigh 10.6 mg of acetylacetonate vanadyl and add it to 200 μL of dimethyl sulfoxide. Stir to dissolve and obtain a dimethyl sulfoxide solution of acetylacetonate vanadyl.
[0056] The BiOI / FTO precursor electrode obtained in step (2) was placed in a muffle furnace and heated to 60 °C. Then, a dimethyl sulfoxide solution of vanadium acetylacetonate was added dropwise to the surface of the BiOI / FTO precursor electrode. After the addition was completed, the temperature was further increased to 450 °C for calcination and held for 120 min.
[0057] After calcination, the electrode was allowed to cool naturally to room temperature. It was then immersed in a 3 mol / L KOH solution for 30 min to remove surface impurities. Subsequently, it was washed sequentially with deionized water and anhydrous ethanol, and dried at room temperature to obtain the desired electrode. Photoelectrode.
[0058] The amount of dimethyl sulfoxide solution of acetylacetone vanadium oxide added was: three drops, each about 50 μL, for a total of 150 μL; the alkaline washing solution was 3 mol / L KOH; and the calcination program was 450 ℃ for 120 min.
[0059] (4) Fabrication of photoelectrodes
[0060] Weigh 60 mg of dopamine hydrochloride and 79 mg of Tris-HCl, add them to 50 mL of deionized water, and stir to dissolve. Then adjust the pH to 8.5 with 3 mol / L NaOH solution to obtain Tris-HCl buffer containing dopamine hydrochloride.
[0061] The result obtained in step (3) The photoelectrode was immersed in the Tris-HCl buffer solution containing dopamine hydrochloride, under simulated sunlight AM 1.5G and light intensity. Under stirring conditions for 2 hours, dopamine was allowed to... Photoinduced polymerization occurred on the surface, forming a PDA-modified layer. After treatment, the electrode was removed and dried in a vacuum drying oven at 70 °C for 24 h to obtain... Photoelectrode.
[0062] The Tris-HCl buffer solution containing dopamine hydrochloride can be sonicated for 30 minutes before use to improve solution homogeneity.
[0063] (5) Preparation of photoelectrocatalytic materials
[0064] Prepare an electrolyte containing 0.4 mM ferrous acetate and 0.04 mM nickel acetate. The electrolyte obtained in step (4) is then... The photoelectrode is immersed in the electrolyte, and pulsed photoelectrode deposition is performed under the condition that the reversible hydrogen potential VRHE is 0 V.
[0065] The pulsed photoelectrodeposition was performed under AM 1.5G illumination and illumination intensity. The deposition was carried out under the following conditions: light cycle of 10 s on, 20 s off, and deposition time of 20 min. After deposition, the electrode was removed, rinsed with deionized water, and dried to obtain... Photocatalytic materials.
[0066] income In photoelectrocatalytic materials, the PDA modification layer is located in Between the layer and the NiFeOx cocatalyst layer, a functional bridging layer is used to improve... The interfacial bonding with NiFeOx promotes the transfer of photogenerated holes to the surface cocatalyst, thereby reducing surface charge recombination and improving photoelectrocatalytic stability.
[0067] Example 2
[0068] The difference between this embodiment and Embodiment 1 is that in step (1), the material is... 10 μL of 69% nitric acid was added to the mixed solution to adjust the pH to 2.0. The remaining steps were the same as in Example 1. The sample of Example 2 was denoted as... .
[0069] income The morphology, crystal phase, and photoelectrocatalytic performance of the photoelectrocatalytic material can be characterized according to Test Examples 1 to 4.
[0070] Compared to Example 1, this example illustrates the effect of the pH of the BiOI electrodeposition solution on the deposition morphology of the BiOI precursor. The impact of crystal growth on the final photoelectrocatalytic performance. For example... Figure 6 As shown, the sample exhibits a high and stable photocurrent response in the stability test, with an initial photocurrent density of approximately [value missing]. The stability retention rate is approximately 99.7%. Compared to its slightly lower photocurrent density and slightly lower stability retention rate, both exhibit excellent stability close to 100%, indicating that the sample still has good interfacial stability and continuous photoelectric response capability under pH 2.0 conditions.
[0071] Example 3
[0072] The difference between this embodiment and Embodiment 1 is that in step (2), when electrodepositing BiOI on the FTO conductive glass surface, electrodeposition is stopped when the electrodeposition charge reaches 0.65 C; the remaining steps are the same as in Embodiment 1. The sample of Embodiment 3 is denoted as... .
[0073] This example illustrates the effect of BiOI deposition amount on The effects of layer thickness, surface roughness, light absorption capacity, and carrier transport performance. The SEM image of this sample is shown below. Figure 1 As shown in the figure, this indicates that setting the electrodeposition charge to 0.65 C does not significantly alter the morphology of the material. According to... Figure 7 The Jt curve can be obtained The initial photocurrent density is The stability retention rate after 10 hours was approximately 99.6%, slightly lower than... .from Figure 8 It can be known that, The impedance arc radius of the sample is significantly smaller than This indicates that its interfacial charge transfer impedance is lower, and the charge transport process at the electrode / electrolyte interface is smoother. In contrast, The semicircle is larger, and in The more pronounced directional extension indicates that the sample possesses higher interfacial impedance and relatively slower charge transfer kinetics. A smaller impedance arc typically signifies suppressed recombination of photogenerated carriers at the interface, which is beneficial for improving carrier separation and transport efficiency during the photoelectrochemical reaction. Therefore, these EIS results demonstrate... It has superior interfacial charge transport capabilities, which is consistent with its better photoelectrochemical performance.
[0074] Comparative Example 1
[0075] This comparative example provides a... The photoelectrode is prepared using the same method as steps (1) to (3) in Example 1, without the PDA modification in step (4) or the NiFeOx loading in step (5). The resulting material is denoted as... .
[0076] After testing, It exhibited a photocurrent density of 1.37 and a stability retention rate of 46% after 10 h during the photoelectrocatalysis process. Compared with Example 1, The photocurrent density is low and the stability is poor, indicating that alone Photoelectrodes suffer from problems such as rapid recombination of photogenerated carriers, slow surface reaction kinetics, and insufficient stability.
[0077] Test Example 1: Morphological and Structural Characterization
[0078] The morphology of the photoelectrode obtained in Example 3 was observed using a scanning electron microscope. The results showed that... Figure 1 As can be seen in b, the surface of the BVO sample exhibits an interconnected porous structure of nanoparticles / short rods; after PDA modification, as shown in... Figure 1 As shown in a, the PDA / BVO still maintains The original nanoporous framework did not exhibit significant aggregation or structural collapse. Furthermore, the PDA / BVO surface was rougher than that of BVO, with some coating or bridging characteristics between particles. This indicates that the PDA modification did not disrupt the original structure. The basic nanostructure, after being modified with PDA, A uniform PDA modification layer is formed on the surface; after further loading of NiFeOx, as shown... Figure 1 As shown in c, NiFeOx is uniformly distributed in Surface but not damaged The basic nanostructure.
[0079] Figure 2 In the XRD patterns, the main diffraction peaks of PDA / BVO and BVO in Example 1 are basically the same, indicating that after PDA modification... The main crystalline phase remains stable. No obvious new impurity phase peaks appeared in PDA / BVO, indicating that the PDA modification process did not damage the crystalline phase. Due to its crystal structure, PDA itself may be an amorphous layer or have a low content, thus not forming obvious diffraction peaks in XRD. Figure 2The XPS peak profiles show changes in the elemental composition and chemical state of the PDA / BVO surface. Characteristic signals or peak shape changes related to C, N, and O can be observed in the PDA / BVO, indicating the introduction of carbon- and nitrogen-containing functional groups into the PDA. Surface variations in the position or shape of Bi, V, O, and other related peaks can also indicate the relationship between PDA and [other components / elements]. There are interfacial interactions between the surfaces, rather than simple physical mixing. That is, the PDA was successfully modified... The surface, and PDA modification will not change The main crystalline phase; the oxygen- and nitrogen-containing functional groups in PDAs may be related to... Surface interactions occur, thereby improving interfacial charge transport and material stability.
[0080] Test Example 2: Light Absorption and Photoelectric Conversion Performance Test
[0081] The light absorption performance of Example 1 was tested using ultraviolet-visible diffuse reflectance spectroscopy. The results showed that the light absorption performance of Example 1 was... Photoelectrocatalytic materials have good light absorption capabilities in the visible light region.
[0082] The photocurrent response was tested using a three-electrode system, with the photoelectrode under test as the working electrode, a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The light source was a 150 W xenon lamp, the test voltage was -0.1 V, and the test time was 36000 s.
[0083] Test Results Figure 3 The results show a difference in photoresponse / photocapture capability between PDA / BVO and BVO. PDA / BVO exhibits higher or more persistent light absorption response over a wider wavelength range, indicating that the visible light absorption capability of the PDA-modified material is enhanced, and the absorption edge is extended to some extent. Figure 3 The curve on the right shows that the overall photoelectric conversion efficiency of PDA / BVO is higher than that of BVO, and it maintains better conversion performance in the visible light response range. This indicates that PDA modification not only improves light absorption but also promotes photogenerated electron-hole separation, reduces carrier recombination, and improves photoelectric conversion efficiency. In other words, PDA modification can enhance... The light-harvesting ability is improved, and its photoelectric conversion efficiency is enhanced; PDA / BVO has better visible light response and carrier utilization compared to unmodified BVO.
[0084] Figure 4As can be seen, the band gap of BVO is approximately 2.44 eV, while that of PDA / BVO is approximately 2.36 eV. The band gap of the material modified with PDA decreased from 2.44 eV to 2.36 eV, further demonstrating that PDA modification reduces the band gap. The absorption edge undergoes a red shift, enhancing the utilization of visible light. In other words, PDA modification can modulate... The band structure is modified to reduce the band gap, thereby improving the material's response to visible light.
[0085] Test Example 3: Long-term stability test
[0086] The results obtained in Example 1 The photoelectrocatalytic material was placed at room temperature and pressure for 10,000 hours, and then the it photocurrent was tested again according to the method in Test Example 2, and the results were compared with those before placement.
[0087] Test results show that the photocurrent density of the material obtained in Example 1 after 36000 s testing before placement was [value missing]. After being placed for 10,000 hours, the photocurrent density was tested again. The photocurrent retention rate was 86.3%.
[0088] The above results demonstrate that the invention yields... Photoelectrocatalytic materials exhibit excellent long-term stability. The PDA modification layer can protect them to some extent. Photoelectrode reduces photocorrosion and enhances the interaction between NiFeOx cocatalyst and... The surface bonding stability is improved, thus achieving long-term stable photoelectrocatalytic performance. The 10,000-hour storage conditions included a temperature of 26°C, humidity of 70%, protection from light, and exposure to air.
[0089] Figure 5 The photocurrent changes of PDA / BVO-loaded NiFeOx photocatalysts with resting time were compared with those of BVO-loaded NiFeOx. The figures show that the photocurrent of the unmodified BVO-loaded NiFeOx sample significantly decreased with resting time; while the photocurrent of the PDA / BVO-loaded NiFeOx sample remained relatively stable with a smaller decrease. That is, the PDA modification layer can significantly improve… Long-term stability after loading NiFeOx is improved, and photocurrent attenuation during rest or long-term use is reduced. The PDA may act as an interface protective layer and bridging layer, protecting... It protects against photocorrosion and, on the other hand, enhances the interaction between NiFeOx and... Surface bonding stability.
[0090] This invention is achieved through By combining photoelectrode construction, photo-induced PDA interface modification, and NiFeOx pulsed photoelectrode deposition, a method was adopted to obtain a product with good photoelectrocatalytic activity and long-term stability. Composite photoelectrocatalytic materials.
[0091] in, As a visible-light-responsive semiconductor material, it can absorb visible light and generate photoelectrons and holes. The PDA modification layer can improve the surface interface properties, promote hole transport, and enhance material stability. The NiFeOx cocatalyst can provide active sites for water oxidation, reduce the overpotential of the water oxidation reaction, and accelerate the surface reaction kinetics. The synergistic effect of these three factors enables the material of this invention to exhibit high photocurrent density, low interfacial transport impedance, and excellent long-term stability in the photoelectrocatalysis process.
Claims
1. A PDA modification The photoelectrocatalytic material, characterized in that, Includes a conductive substrate and a substrate loaded on the surface of the conductive substrate. Nanoparticle layer, formed in the A PDA modification layer on the surface of the nanoparticle layer and a NiFeOx cocatalyst layer supported on the PDA modification layer; The PDA modification layer is located in the Between the nanoparticle layer and the NiFeOx cocatalyst layer, and respectively with the... The nanoparticle layer is in contact with the NiFeOx cocatalyst layer.
2. The PDA modification according to claim 1 The photoelectrocatalytic material, characterized in that, The The layer has a porous structure composed of interconnected nanoparticles and / or short nanorods; The PDA modification layer is formed by dopamine under light conditions. Polymerization occurs on the surface of the layer, forming a layer that at least partially covers the surface. The surface of the layer; The PDA modification layer is used to connect the The layer and the NiFeOx cocatalyst layer, and promote the Photogenerated holes generated in the layer are transferred to the NiFeOx cocatalyst layer; The conductive substrate is FTO conductive glass; The nanoparticle layer is formed by introducing a vanadium source into the BiOI precursor and then calcining and converting it; the PDA modification layer is formed by photoinduced polymerization of dopamine hydrochloride in Tris-HCl buffer solution with pH 8.0-9.0; the NiFeOx cocatalyst layer is formed by pulse photoelectrodeposition of an electrolyte containing iron and nickel salts.
3. A PDA modification A method for preparing photoelectrocatalytic materials, characterized in that, Includes the following steps: S1, with KI and Dissolve in deionized water, and add nitric acid to adjust the pH to obtain mixed solution A; S2, dissolve p-benzoquinone in anhydrous ethanol to obtain solution B; S3, add solution B dropwise to mixed solution A and stir to obtain BiOI electrodeposition solution; S4, using a conductive substrate as the working electrode, electrodeposition is performed in the BiOI electrodeposition solution to obtain a conductive substrate with BiOI nanoparticles deposited on its surface. S5, a vanadium source is introduced onto the surface of a conductive substrate with deposited BiOI nanoparticles, followed by calcination and impurity removal to obtain... Photoelectrode; S6, the The photoelectrode was immersed in a Tris-HCl buffer solution containing dopamine hydrochloride and subjected to photo-induced treatment under simulated sunlight to obtain... Photoelectrode; S7, the The photoelectrode was immersed in an electrolyte containing iron and nickel salts, and pulsed photoelectrodeposition was performed under cyclic illumination to obtain a NiFeOx-loaded PDA-modified PDA. Photocatalytic materials.
4. The preparation method according to claim 3, characterized in that, In step S1, the KI, The mass-to-volume ratio of the deionized water is 1.68 g: 0.4–1.0 g: 25 mL; adjust the pH to 1.5–2.
0.
5. The preparation method according to claim 3, characterized in that, In step S2, the mass-to-volume ratio of p-benzoquinone to anhydrous ethanol is 0.2–4.0 g: 10 mL; in step S3, solution B is added dropwise to mixed solution A at a rate of 0.5–2 mL / min.
6. The preparation method according to claim 3, characterized in that, In step S4, the conductive substrate is FTO conductive glass, and the electrodeposition is performed using a three-electrode system, wherein the FTO conductive glass is used as the working electrode, the Pt wire is used as the counter electrode, and the Ag / AgCl electrode is used as the reference electrode; the applied bias voltage for electrodeposition is -0.05 V to -0.15 V, and the electrodeposition charge is 0.6 to 0.8 C.
7. The preparation method according to claim 3, characterized in that, In step S5, the vanadium source is a dimethyl sulfoxide solution of vanadium acetylacetonate; the calcination temperature is 400–500 °C, and the calcination time is 90–180 min; after calcination, the vanadium is soaked in NaOH or KOH solution to remove impurities.
8. The preparation method according to claim 3, characterized in that, In step S6, the Tris-HCl buffer solution containing dopamine hydrochloride is prepared as follows: dopamine hydrochloride and Tris-HCl are dissolved in deionized water, and the pH is adjusted to 8.0–9.0; the simulated sunlight is AM 1.5G, and the light intensity is [missing information]. The photo-induced treatment time is 1–4 h.
9. The preparation method according to claim 3, characterized in that, In step S7, the iron salt is ferrous acetate and the nickel salt is nickel acetate; the concentration of the iron salt in the electrolyte is 0.1–1.0 mM and the concentration of the nickel salt is 0.01–0.2 mM; the pulsed photoelectrodeposition is performed under the condition of a reversible hydrogen potential of 0 V, the light cycle is 5–20 s on and 10–40 s off, and the deposition time is 10–40 min.
10. The PDA modification according to claim 1 or 2 The photoelectrocatalytic material, or the PDA-modified material prepared by the preparation method according to any one of claims 3 to 9. Applications of photoelectrocatalytic materials in photoelectrocatalytic water oxidation, photoelectrocatalytic oxygen evolution reaction, pollutant degradation, or photoelectrocatalytic organic synthesis reactions.
